ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL - B21108003, JOAN AYU RETNO.PS (Jurnal Curvanomic, 2012)
Banking industry either syariah or conventional bank are part of national banking system which have the significant roles in Indonesian economic. This research is performed to compare the financial performance of syariah and conventional bank as seen on Capital Adequacy Ratio (CAR), Return On Asset (ROA) and Loan to Deposit Ratio (LDR) point of views and also to know whether there is difference in the financial performance based on those three points of views. There are forur syariah banks and four conventional banks which are used as samples in this research. Sampling technique employed in this research is purposive judgement sampling. Paired Sample T test is used as analysis technique to know whether there is difference in the financial performance of syariah and conventional bank. The result of this research shows that the difference in the financial performance happens in Return On Asset (ROA) and Loan to Deposit Ratio (LDR) point of views, while from CAR point of view there is no difference. CAR, ROA and LDR of conventional bank are better than syariah bank. All conventional banks can be classified as healthy and having a good financial performance while there are syariah bank which suffer in financial loss, in unhealthy financial stage, and illiquid. Keywords: Syariah Bank, Conventional Bank, Capital Adequacy Ratio (CAR), Return On Asset (ROA) and Loan to Deposit Ratio (LDR)